Biomechanical mechanism and clinical management progress of surgical wound tension - Gong, Feiyu; Wan, Bingjie; Qi, Ping; Wei, Zairong (Frontiers in Surgery, 2025)
Surgical wound tension, a core biomechanical factor in tissue repair, is clinically important because high tension can cause microcirculatory disturbances, leading to inhibition of cell migration and collagen deposition, and increasing complications such as wound dehiscence and incisional hernia. Therefore, the concept of “active tension reduction” has been emphasized, including preoperative optimization of biomechanical distribution, intraoperative layered combined subcutaneous tension-reducing suturing, and postoperative dynamic management. However, the difficulty in standardizing wound tension quantification presents clinical challenges. In summary, this study integrates the biomechanical mechanisms of surgical wound tension with clinical practice to explore a systematic strategy from tension assessment to novel intervention techniques.